2011
DOI: 10.1111/j.1365-2605.2011.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen variation in a population of fertile donors: evaluation in a French centre over a 34‐year period

Abstract: Although it has been suspected that there is a decrease in semen quality over time, the results reported to date remain debatable because of methodological issues. The aim of the study reported here was to investigate the evolution of semen quality over time in a population of 1114 fertile candidates for sperm donation at CECOS, Tours, between 1976 and 2009. We investigated semen volume, sperm concentration, progressive motility, vitality, percentage of normal forms and multiple abnormalities index of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…Splingart et al . () reported a significant decrease in total sperm count, motility, viability and normal forms in Tours, France from 1976 to 2009. Similarly, Rolland et al .…”
Section: Discussionmentioning
confidence: 99%
“…Splingart et al . () reported a significant decrease in total sperm count, motility, viability and normal forms in Tours, France from 1976 to 2009. Similarly, Rolland et al .…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of reduced-quality semen together with the increasing age at which women decide to get pregnant may explain the reduced fecundity of populations from several countries [32,35]. In fact, the decline in sperm counts in recent decades has been reported in numerous studies [3,36], although not all authors have observed this trend [5,37]. If the trend is real, the ageing process could be accelerated at the level of whole populations, which would create serious medical as well as socio-cultural threats to many societies (especially in ageing Europe).…”
Section: Prace Oryginalnementioning
confidence: 99%
“…There is an ongoing discussion regarding the decline of the number and quality of spermatozoa in humans [1][2][3]. This phenomenon is of special importance in the context of worrisome demographic trends in developed countries and because male factors may play a role in 40% of infertile couples [4].…”
Section: Introductionmentioning
confidence: 99%
“…According to two meta‐analyses, seminal parameters, which are predictors of male fertility potential, have been declining over time worldwide (Carlsen, Giwercman, Keiding, & Skakkebaek, ; Swan & Elkin, ), and recent studies have corroborated this finding (Borges, Setti, Braga, Figueira Rde, & Iaconelli, ; Fernandez et al, ; Sengupta, Dutta, & Krajewska‐Kulak, ; Splingart et al, ). This decline in semen quality is likely multifactorial, and a variety of lifestyle factors have been proposed to influence spermatogenesis and reproductive function, either positively (Gaskins, Colaci, Mendiola, Swan, & Chavarro, ; Minguez‐Alarcon et al, ) or negatively (Braga et al, ; Gaskins et al, ; Joo, Kwon, Myung, & Kim, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 98%